Mamasab Bakery / Muhammad Abid Kamaruddin ... [et al.] - Kamaruddin, Muhammad Abid; Abdul Shukor, Saidatul Nor Shakirah; Saiful Azmi, Nur Shuhada; Zainal, Nur Shafiqah; Salleh, Aqilah (2021)
This study case was conducted to examine Mamasab Bakery SWOT analysis and identify the problems that are faced by the business. It also contains suggested solutions that can be taken by Mamasab Bakery to encounter the issues and to improve its business. Mamasab has two categories of products which are bakery and cosmetic. There are multiple types of marketing techniques used by Mamasab to spread its brand awareness. For instance, through social media, blogging, television, partner third-party, do contests, promotion and provide online ordering. Next, the results of the research done shows Mamasab strength, weakness, opportunities and threat. Positive internal factors that Mamasab have is its used high-quality materials to produce the products, powerful marketing group and implementation of zero marketing strategies. While, internal factors that could bring negative impact to Mamasab is it is a sole proprietorship business, hardship to meet customer requests due to short supply and barriers for the customers to purchase its product. On the other hand, for external factors that would bring positive impact to Mamasab’s business is the opportunities for Mamasab to form collaboration with other well-known brands, the thrive demand from consumers for cosmetic and skincare products, chances to launch its branches that will cover every state in Malaysia, ability to easily get the dropship for the products and the ease of access of resources on the internet. While the external factors that would cause negative impact to Mamasab’s business are many competitors that come from the same market segment as Mamasab, the appearance of innovative products from close competitors and lastly is customers' purchasing habits. Hence to encounter the issues, there are several solutions that Mamasab can imply in its business. For example, to tackle its weakness, Mamasab could enhance its skills in handling the management and finance, preserve the relationship with the supplier and buyers and develop new strategies to improvise its ordering system. Besides, to face the threats, Mamasab must carry out more collaboration with other brands to produce better and innovative products, broaden its branches by launching more small branches in new places and attempt to understand the customer’s expectation of the products by conducting online surveys.